REKONSTRUKSI PARADIGMA DAKWAH: Dalam Konteks Pendekatan Manajemen Fungsional Dakwah Bil-Hal Di Pedesaan - Amin Tohari (LP2M Universitas Ibrahimy, 2015)
Why Indonesia still need to IMF. The answer is unsufficient ability to manage its selves. The implications of propaganda is the primary awareness of importance caring human-social. A caring the social is what can make the movement of empowerment of rural communities. Edward de Bono, that in the future people should be more constructive. Humans must be more creative. Future, the globalization problem more complex. So people are required more creative and constructive. Exactly is dakwah bil-hal is dakwah bi-lisanil-hal by social action.